Denaturing gradient gel electrophoresis profiles of 16S rRNA-defined populations inhabiting a hot spring microbial mat community. - Ferris, M J (1996)
Denaturing gradient gel electrophoresis (DGGE) of PCR-amplified 16S rRNA gene segments was used to profile microbial populations inhabiting different temperature regions in the microbial mat community of Octopus Spring, Yellowstone National Park. DGGE allowed a rapid evaluation of the distributions of amplifiable sequence types. Profiles were essentially identical within regions of the mat defined by one temperature range but varied between sites with different temperature ranges. Individual DGGE bands were sequenced, and the sequences were compared with those previously obtained from the mat by cloning and from cultivated Octopus Spring isolates. Two known cyanobacterial populations and one known green nonsulfur bacterium-like population were detected by DGGE, as were many new cyanobacterial and green nonsulfur and green sulfur bacterium-like populations and a novel bacterial population of uncertain phylogenetic affiliation. The distributions of several cyanobacterial populations compared favorably with results obtained previously by oligonucleotide probe analyses and suggest that adaptation to temperature has occurred among cyanobacteria which are phylogenetically very similar.